Year of the tiger : an activist's life - Wong, Alice, 1974- (Vintage Books, a division of Penguin Random House LLC, 2022)
Drawing on a collection of original essays, previously published work, conversations, graphics, photos, commissioned art by disabled and Asian American artists, and more, Alice uses her unique talent to share an impressionistic scrapbook of her life as an Asian American disabled activist, community organizer, media maker, and dreamer. From her love of food and pop culture to her unwavering commitment to dismantling systemic ableism, Alice shares her thoughts on creativity, access, power, care, the pandemic, mortality, and the future. As a self-described disabled oracle, Alice traces her origins, tells her story, and creates a space for disabled people to be in conversation with one another and the world. Filled with incisive wit, joy, and rage, Wong's Year of the Tiger will galvanize readers with big cat energy.